Surfactant and dopant addition effect on optical and structural properties of ZnSe (Te) nanostructured semiconductors - Valluzzi, Lucas Gabriel (2020)
ZnSe and ZnTe nanoparticles were obtained by mechanical milling. The influence of surfactant and doping agent addition on structural and optical properties were analyzed. X-ray diffraction (XRD) confirmed cubic crystalline structure is maintained for all milling times and the progressive substitutional incorporation of Al atoms into the Zn-based semiconductor structure. The agglomerate state of milled powders was disclosed by scanning electron microscopy (SEM), and Dispersion Light Scattering (DLS). Positron annihilation lifetime (PALS) spectroscopy allowed to identify the defects induced by mechanical work. A slight shift on the energy band gap with respect to pure semiconductor nanoparticles was revealed from optical diffuse reflectance measurements for all studied samples. The obtained results agree with first-principles calculations based on the Density Functional Theory (DFT). The calculations predict that Al substitute the Zn atom in the ZnTe and ZnSe lattice and a zinc vacancy must appear in order to recover the semiconductor character, as shown (or suggest) the experimental results. The characteristic positron annihilation lifetimes for the doped samples are obtained for both systems and compared with those measured. This theoretical approach helps us to deeper understand the origin and characteristics of different positrons traps.